(untitled) (Research, Society and Development, 2020)
Objective: describe the experience of the practice of health education lived by a nursing student through educational actions carried out with students. Methodology: This is an experience report that took place between the years 2019 and 2020 in the municipalities of Irecê-Ba and Cafarnaum-Ba, from educational activities aimed at schoolchildren enrolled from the 1st to the 5th year of elementary school in a school private and public in the municipalities mentioned above. Results: The development of educational activities was based on dialogues focused on the benefits of healthy eating and the practice of activities to promote health and prevent childhood obesity. It was possible to notice that students from both schools demonstrated knowledge in educational actions about the benefits of healthy eating for maintaining health. In addition, it was possible to understand that health education is essential for reflection and behavior change in the lives of individuals, and the school is considered an important space for the development of knowledge and integration of students’ learning with the community, which have great potential for disseminating fundamental information for health promotion. Final Considerations: The professional nurse has an important role in health education, experience has shown how health education is important for the promotion and prevention of diseases since childhood.